2011
DOI: 10.1115/1.4000488
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Flow Control to an Aft-Loaded Low Pressure Turbine Cascade With Unsteady Wakes

Abstract: The synchronous application of flow control in the presence of unsteady wakes was studied on a highly loaded low pressure turbine blade. At low Reynolds numbers, the blade exhibits a nonreattaching separation bubble under steady flow conditions without upstream wakes. Unsteady wakes from an upstream vane row are simulated with a moving row of bars. The separation zone is modified substantially by the presence of unsteady wakes, producing a smaller separation zone and reducing the area-averaged wake total press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…An evident variation of the boundary layer growth can be observed behind s/s max = 0.85. This feature suggests that wake effects induce transition of the boundary layer behind s/s max = 0.85, while upstream of this position an intermittent switch from the laminar to the turbulent state is expected to occur as a consequence of the periodic incoming wake perturbation [23]. The boundary layer thickness at the blade trailing edge is sensibly higher in the unsteady case as compared with the attached steady one (at high FSTI), since the transition process is shifted upstream by wake effects.…”
Section: Piv Measurements: Unsteady Inflow Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…An evident variation of the boundary layer growth can be observed behind s/s max = 0.85. This feature suggests that wake effects induce transition of the boundary layer behind s/s max = 0.85, while upstream of this position an intermittent switch from the laminar to the turbulent state is expected to occur as a consequence of the periodic incoming wake perturbation [23]. The boundary layer thickness at the blade trailing edge is sensibly higher in the unsteady case as compared with the attached steady one (at high FSTI), since the transition process is shifted upstream by wake effects.…”
Section: Piv Measurements: Unsteady Inflow Resultsmentioning
confidence: 96%
“…In a real machine, the understanding of the effects due to the FSTI is further complicated by the rotor-stator aerodynamic interaction, which strongly alters the dynamics of the separation process (if any) [22][23][24], as well as of the by-pass transition process in the case of attached flows. Indeed, incoming wakes carry high frequency velocity fluctuations that interact with the stability characteristics of the boundary layer developing between wakes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The available literature about the SJ application in lowpressure turbines is still limited, and to the authors' knowledge, few experimental works Bons et al 2008) describe the boundary layer separation/transition processes when incoming wakes and active devices are simultaneously present and act to control separation. In these works, phase-locked hot-wire and PIV measurements were used by the authors to document the dynamics of the separation zone when subjected to synchronized unsteady forcing by a spanwise row of vortex generator jets in addition to unsteady wakes.…”
Section: CLmentioning
confidence: 99%
“…The plenum shapes in the airfoils used by Bourgois et al were trapezoidal while the L1A plenum in this work was a cylinder of 11-mm diameter. Bons et al (2008a) observed overshoot in the VGJ pulse history and significant rms fluctuations in the exit profile at a single VGJ location for the L1A model used in this work. However, the consequence of employing a Fig.…”
Section: Jet Visualizationmentioning
confidence: 89%
“…Images were acquired by phase-locking the excitation light to the pulsing frequency of the VGJs. The pulsing frequency of the jets in this study was set to 10.6 Hz (T = 94 ms), a value which had been used in previous experiments while using the upstream rotor wake generator in the facility (Bons et al 2008a). Pulsing was accomplished with a General Valve Inc. Iota One unit, which was set to pulse the jets on a 30% duty cycle.…”
Section: Low-speed Cascade Tunnel and Instrumentationmentioning
confidence: 99%